An energy-efficient dynamic positioning controller for high sea conditions. (December 2022) - Alagili, Osama; Khan, Mohammad Aminul Islam; Ahmed, Salim; Imtiaz, Syed; Zaman, Hasanat; Islam, Mohammed
Abstract: In constantly changing high sea environments characterized by large waves, turbulent surface currents, and high wind gusts, a dynamic positioning (DP) system with enhanced positioning capabilities is becoming essential. The controller in a DP system calculates the force needed by the propellers and thrusters to counteract environmental forces and keep the vessel at its desired position. In addition to maintaining the position, minimizing the thruster demand is another control objective pursued by a type of controllers, termed as energy-efficient DP or the so-called "Green DP". In line with this objectives, the present work proposes a controller that minimizes thruster demand while maintaining position constraints. This novel energy-efficient controller (i.e.,  like Green-DP) exploits the structure of the economic nonlinear model predictive controller (ENMPC) and adopts "green" objectives and performance metrics, including thruster energy efficiency. The MATLAB/Simulink simulator and toolbox add-ons were used in a simulation environment to demonstrate the performance of the proposed energy efficient DP, called Green-NMPC. The controller was tested for moderate to high sea wave conditions. The controller reduced up to 50% thruster demand in sway direction compared to NMPC while maintaining the vessel positioning objectives. Highlights: An energy efficient dynamic positioning controller structure is proposed. The proposed controller is based on the theory of Economic Nonlinear Model Predictive Controller (ENMPC). The controller was implemented and tested for moderate to harsh sea conditions. The controller demonstrated lower thruster demand while maintaining vessel position.